Female orgasmic dysfunction and severe climacteric symptomatology in women aged 40 to 59 years: an independent association from an analysis of a multicenter Latin American study. Issue 6 (7th June 2022) - Urrunaga-Pastor, Diego; Mezones-Holguin, Edward; Blümel, Juan E.; Apolaya-Segura, Moises; Barón, German; Belzares, Emma; Bencosme, Ascanio; Calle, Andres; Espinoza, Maria T.; Flores, Daniel; Izaguirre, Humberto; León-León, Patricia; et al.
Abstract: Objective: To evaluate the association between the severity of climacteric symptoms (CS) and orgasmic dysfunction (OD), controlled by demographic, clinical, and partner variables. Methods: We carried out a secondary analysis of a multicenter Latin American cross-sectional study that surveyed sexually active women 40 to 59 years old. We assessed CS (global, somatic, psychological, or urogenital domains) and OD. Also, we explored clinical variables and partner sexual conditions. We performed logistic regression models with nonparametric bootstrap resampling to estimate crude and adjusted odds ratios (aOR) with 95% confidence intervals (CI). Results: We included data of 5, 391 women in the analysis. Regarding CS, 24.8%, 10.8%, 28.4%, and 32.9% had respectively severe symptoms according to total, somatic, psychological, and urogenital domain scores of the Menopause Rating Scale. OD was found in 25.4% of women. The adjusted model (including menopausal status and partner sexual dysfunction) showed that severe CS increased the odds of OD (aOR = 2.77; 95% CI: 2.41-3.19 [total Menopause Rating Scale score]; aOR = 1.65; 95% CI: 1.37-2.00 [somatic domain]; aOR = 2.02; 95% CI: 1.76-2.32 [psychological domain] and aOR = 3.89; 95% CI: 3.40-4.45 [urogenital]). Conclusions: Severe CS were associated with OD independently of demographic, clinical, and partner variables. Severe urogenital symptoms had the strongest association.